Neutral point clamped inverter for enhanced grid connected PV system performance based on hexagonal space vector modulation - R. Palanisamy; K. Vijayakumar; Mohammad Imtiyaz Gulbarga; Mohammed Al Awadh; Liew Tze Hui (Scientific Reports)
Abstract The increasing global demand for renewable energy has accelerated the adoption of grid-connected photovoltaic (PV) systems. However, conventional PV inverters often rely on transformers, which add to the system’s cost, size, and power losses. Transformerless inverter topologies have emerged as a promising alternative, offering improved efficiency, compact design, and lower costs. Despite these advantages, challenges such as high total harmonic distortion (THD), common mode voltage (CMV) issues, and neutral current imbalance must be addressed to ensure reliable grid integration. This research investigates a transformerless five-level neutral point clamped (NPC) inverter for grid-connected PV applications, aiming to overcome these challenges. The study focuses on analysing THD, mitigating CMV to enhance system reliability, and optimizing output voltage levels to meet grid standards. The proposed transformerless five-level NPC inverter, incorporating a coupled inductor, is controlled using Hexagonal Space Vector Modulation (HSVM) to improve performance. Additionally, the research evaluates neutral current behavior to ensure stability and compliance with grid codes. Simulation and experimental results validate the proposed system’s effectiveness under varying operating conditions, highlighting its potential as a high-efficiency, cost-effective solution for sustainable energy integration into the grid.